Strategi IMTAQ IAIN Madura dalam Menjaga Hafalan Mahasiswa di Era Disrupsi - Fayruzah El-Faradis; Anisatul Fitri (Universitas Al-Amien Prenduan, 2020)
IMTAQ is one organization in IAIN Madura that participated by students who memorize Al-Quran. In this case, the strategy in memorizing Al-Quran is very important. The focus of this research are: how the strategy of IMTAQ IAIN Madura in memorizing Al-Quran, and what are the obstacles and solutions faced by IMTAQ IAIN Madura in memorizing Al-QuranÂ in disruption era. This research used qualitative approach, the data collection researchÂ used are interview, observation and documentation. Data validity checking used triangulation. The result of this research are: the strategy used by IMTAQ in memorizing Al-Quran are: 1. Conducted memorizing Al-Quran as routine, memorizing test every 1 juz, khotmul quran, scientific studies. Obstacles faced are: similarity time between lectures and IMTAQ activities, lack of regeneration. And the solution is to provide time agreement between muhafidhoh and IMTAQ members.